Pengembangan Media Kartu Kata Bergambar Kontekstual - Nursamsi (Pedagogical Education and Review of Linguistics, 2025)
Indonesian language is the foundation of various other fields of knowledge, with one of its branches being reading skills. However, students often face difficulties in learning to read and frequently lack suitable educational media to meet their needs. Therefore, concrete media in the form of picture-word cards is expected to clearly convey the material, be easy to use, and be engaging for elementary school/MI students. This study aims to assess the need for picture-word card media, describe the steps in developing picture-word card media for reading materials, and evaluate the validity and practicality of the picture-word card media developed for grade I students at MI Muhammadiyah Lasusua. The research employs a Research and Development (R&D) approach, utilizing the ASSURE model with steps including Analyze Learner, State Performance Objective, Select Methods, Media, and Materials, Utilize Media and Materials, Require Learner Participation, and Evaluate and Revise. The results indicate that the development of picture-word card media began with research and initial information gathering through curriculum analysis and student needs assessment. The validity of the picture-word card media was positively rated, with design experts giving a score of 68.75% in the valid category, and content experts also rating 68.75% in the valid category. The practicality test yielded very satisfying results, with an overall score of 85.43% from 26 students and 94.23% from one grade I teacher, both falling into the very practical category.